(3bUjOI GdgGTei aj Yde GdchGcHs - (3GdgGTejs ((3eOjfI GdCScfOQjI s)
(3ChdgG (B:s
(3Cbhd hbhd GdUOb ai GdfaS ChbY hai GdMb eG jUZi Edjg hjSeY s
(3BNQgG (B:s
(3hEf ebGe GdRgQI CYdeg NeSI hYTQhf jhekG ajg Ke JSQY JeJ hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs